Impact of variations in the molarity of sodium hydroxide on metakaolin-ground granular blast-furnace slag-based geopolymer concrete - Rahul Kumar; Rajwinder Singh; Mahesh Patel (Advances in Civil and Architectural Engineering)
The present study investigates the optimization of geopolymer concrete mixes with the addition of metakaolin and ground granular blast-furnace slag as binding agents, ensuring a sustainable and eco-friendly alternative to conventional concrete. In this study, different proportions of the input parameters, such as the molarity of sodium hydroxide, ratio of sodium silicate to sodium hydroxide, and ratio of fixed alkali activator to binder have been considered. Attributes such as compressive strength, ultra-sonic pulse velocity, electricity resistance, mass loss, and strength variation due to acid attack for six geopolymer concrete mixes have been evaluated at different ambient curing periods. In addition, the mathematical relationship, i.e., linear regression, between these properties was also evaluated. The results show that a sodium silicate to sodium hydroxide ratio of 1,8; n sodium-hydroxide molarity of 14, and an alkali activator to binder ratio of 0,45 demonstrated the highest strength (43,3 MPa), electrical resistivity (35,1 K.Ohm.cm), and pulse velocity (4,2 km/s) with the minimal effect of H2SO4 solution on mass (1,2 %) and strength (5,8 %). Additionally, statistical analysis indicated a strong relationship of compressive strength with other properties, which improved as the curing days extended from 28 (Avg. R2=0,68) to 56 (Avg. R2=0,74) days. The outcomes of the study are expected to contribute to the advancement of sustainable construction by providing relevant data regarding material selection, ensuring quality, and optimizing geopolymer concrete production with metakaolin and ground granular blast-furnace slag.